2011
DOI: 10.1161/hypertensionaha.110.164780
|View full text |Cite
|
Sign up to set email alerts
|

Early Sympathetic Activation in the Initial Clinical Stages of Chronic Renal Failure

Abstract: Abstract-Direct and indirect indices of neuroadrenergic function have shown that end-stage renal disease is characterized by a marked sympathetic overdrive. It is unknown, however, whether this phenomenon represents a peculiar feature of end-stage renal disease or whether it is also detectable in the early clinical phases of the disease. The study has been performed in 73 hypertensive patients, of which there were 42 (age: 60.7Ϯ1.8 years, meanϮSEM) with a stable moderate chronic renal failure (mean estimated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
197
0
7

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 273 publications
(213 citation statements)
references
References 46 publications
4
197
0
7
Order By: Relevance
“…8 In addition to the reduction in sympathetic nerve activity, there is evidence for a blood pressure-independent renoprotective effect of the drug as demonstrated by a reduced decline of eGFR in CKD patients when compared with an equipotent dose of a calcium channel blocker 8 and by a favorable effect on microalbuminuria in the absence of blood pressure changes in patients with type 1 diabetes mellitus and optimal blood pressure control. 9 Importantly and consistent with the data presented by Grassi et al 6 in this issue, a previous study also found that sympathetic activity remains elevated in CKD patients despite adequate The kidneys are strategically positioned to be both origin and target of increased sympathetic activation. Various forms of renal injury can stimulate afferent sensory nerve fiber signaling to central integrative structures in the brain (1).…”
supporting
confidence: 75%
“…8 In addition to the reduction in sympathetic nerve activity, there is evidence for a blood pressure-independent renoprotective effect of the drug as demonstrated by a reduced decline of eGFR in CKD patients when compared with an equipotent dose of a calcium channel blocker 8 and by a favorable effect on microalbuminuria in the absence of blood pressure changes in patients with type 1 diabetes mellitus and optimal blood pressure control. 9 Importantly and consistent with the data presented by Grassi et al 6 in this issue, a previous study also found that sympathetic activity remains elevated in CKD patients despite adequate The kidneys are strategically positioned to be both origin and target of increased sympathetic activation. Various forms of renal injury can stimulate afferent sensory nerve fiber signaling to central integrative structures in the brain (1).…”
supporting
confidence: 75%
“…Sympathetic activity is already elevated in early phases of chronic renal failure, and the magnitude of sympathetic overdrive increases with disease progression. 22 Evidence also suggests that the afferent sensory renal nerves in response to intra-renal injury have an excitatory influence on central sympathetic outflow. 10 Consequently, renal sympathetic efferent and afferent nerves exert a powerful influence on initiation, development, and maintenance of elevated systemic BP commonly present in patients with renal failure.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis of long-term trials has shown a linear correlation between deterioration in renal function over time and BP (24). Moreover, muscle sympathetic nerve activity (assessed by microneurography) was significantly and inversely correlated with eGFR in hypertensive patients (25). In the Symplicity HTN-2 trial renal function (assessed by serum creatinine, eGFR [MDRD], and cystatin C concentrations) did not change from baseline to 6 months of RDN (13).…”
Section: Discussionmentioning
confidence: 99%